Avoiding Past Mistakes in Unethical Human Subjects Research: Moving From Artificial Intelligence Principles to Practice - Greene, Kristen K.; Theofanos, Mary F.; Watson, Craig; Andrews, Anne; Barron, Eyeisha (Computer (Long Beach, Calif.), 2024)
Artificial intelligence (AI) is increasingly affecting many aspects of our day-to-day lives. Although the benefits of AI to society are potentially transformative, many fear the cost to human rights may be too great without focused attention.